Whey protein stories – An experiment in writing a multidisciplinary biography. (1st December 2016) - Jensen, Tenna; Bechshoeft, Rasmus L.; Giacalone, Davide; Otto, Marie Haulund; Castro-Mejía, Josue; Bin Ahmad, Hajar Fauzan; Reitelseder, Søren; Jespersen, Astrid Pernille
Abstract: This is an experimental, dual-purpose article about whey protein and how to conduct interdisciplinary analyses and writings. On the one hand, this article is a multidisciplinary commodity biography, which consists of five descriptions of whey protein written by the five different research groups involved in the interdisciplinary research project CALM(Counteracting Age-related loss of Skeletal Muscle Mass). On the other hand, it is a meta-analysis, which aims to uncover and highlight examples of how the five descriptions contribute to each other with insights into the contextualisation of knowledge, contrasts between the descriptions and the new dimensions they bring to established fields of interest. The meta-analysis also contains a discussion of interdisciplinary study objects and the usefulness of the multidisciplinary commodity biography as a format for interdisciplinary publications. The article contributes to the field of food studies with a multidisciplinary biography of whey protein – including its sensory qualities and challenges, insights into its cultural history, its nutritional value and effects on the human body and an analysis of how it is perceived by people who consume it. The biography thereby expands upon existing understandings of whey protein while discussing the usefulness of employing the commodity biography format in interdisciplinary writing. Moreover, the article contributes to the field of interdisciplinary research by providing a practical example of a joint publication and reflections upon the existence, interaction and possibilities of monodisciplinary knowledge structures within interdisciplinary studies and publications.